Role of CBNAAT in the diagnosis of extrapulmonary tuberculosis: a prospective cross-sectional study - Rahul Gupta; Ashok Kumar Janmeja; Arjun Kumar; Balbir Singh; Pramod Kumar Shridhar (The Egyptian Journal of Bronchology)
Abstract Background Tubercular lymphadenitis (TBLN) is the most common extrapulmonary tuberculosis (EPTB) followed by tubercular pleural effusion (TPE). The bacteriological confirmation to diagnose EPTB is more difficult due to its paucibacillary nature often leading to delay or misdiagnosis. The role of the CBNAAT test for the diagnosis of EPTB is highly variable among different populations. Hence, the aim of the present study was to evaluate the role of CBNAAT in the diagnosis of EPTB in a tertiary care center in north India. Methods This was a cross-sectional study conducted in the 100 stable patients of EPTB (55 TPE and 45 TBLN) who came to the Respiratory Medicine Department in MMMC&H, Solan, India. The total duration of the study was eighteen months from April 2021 to September 2022. Fine needle aspirate and pleural fluid samples were collected from all suspected TPE and TBLN patients respectively and were subjected to CBNAAT investigation. All other recommended investigations used for diagnosis of TBLN and TPE were also performed including ZN stain, FNAC, biochemical analysis of pleural fluid, Mantoux test, radiological imaging, and other routine investigations. The data analysis was done using SPSS version 20 software. Results Out of 100 patients of EPTB, 55 were TPE, and 45 were TBLN patients. The positivity of CBNAAT was higher in TBLN patients (57.8%) as compared to TPE (23.7%) patients. The correlation between CBNAAT and ZN stain was statistically significant in both TBLN (p = 0.008) and TPE (p = 0.001) patients. The correlation of CBNAAT with FNAC, duration of illness, erythrocyte sedimentation rate (ESR), and Mantoux were all statistically significant (p < 0.05). Conclusion Our study finding showed higher positivity of CBNAAT in the TBLN as compared to that in patients of TPE. The positivity of CBNAAT in the TBLN patients was higher in pus and cheesy FNAC samples, Mantoux-positive patients, and those with high ESR value.